Large leaking descemetocele presenting as a traumatic corneal laceration - Logeswary K,; Jemaima Che-Hamzah,; Aida Zairani Mohd. Zahidin, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
A 47-year-old healthy Indonesian gentleman, presented with blurring of vision on the left eye associated with pain and redness after history of foreign body entering the eye. A general practitioner prescribed him some eye drops; however, his symptoms worsened. A corneal laceration wound measuring 0.5 x 3.5mm with a large stromal abscess measuring 9.0 x 5.0mm with flat anterior chamber was seen on the left eye. Emergency corneal T&S revealed a large descemetocele and cyanoacrylate corneal glue was applied on the area. C&S showed Pseudomonas aeruginosa. Patient was subsequently undergone penetrating keratoplasty as a definitive measure. This case highlights the rapid progression of pseudomonas keratitis, presented with a large descemetocele, which can be mistaken as an infected corneal laceration wound. Corneal cyanoacrylate glueing together with corneal suturing is a viable temporary method for large descemetoceles awaiting definitive surgery.